Erythrocyte concentrations of chromium, copper, manganese, molybdenum, selenium and zinc in subjects with different physical training levels. Issue 1 (9th July 2020) - Maynar, M.; Grijota, F. J.; Siquier-Coll, J.; Bartolome, I.; Robles, M. C.; Muñoz, D.
Abstract: Background: The aim of the present study was to determine changes occurring in the erythrocyte concentrations of chromium (Cr), copper (Cu), manganese (Mn), molybdenum (Mo), selenium (Se) and zinc (Zn) in male subjects with different training levels living in the same region (Spain). Methods: Thirty sedentary subjects (24.34 ± 3.02 years) formed the control group (CG); 24 moderately trained (4–7 h/week) subjects (23.53 ± 1.85 years) formed the group with a moderate degree of training (MTG) and 22 professional cyclists (23.29 ± 2.73 years), who performed more than 20 h/week of training, formed the high-level training group (HTG). Erythrocyte samples were collected from all subjects in fasting conditions, washed and frozen at − 80 °C until analysis. Erythrocyte analysis of trace elements was performed by inductively coupled plasma mass spectrometry (ICP-MS). Results: The results showed that there was a statistically significant lower erythrocyte concentration of Cu, Mn, Mo and Zn in the MTG and HTG than CG. Se was only significantly lower in HTG than CG. The correlation analysis indicates that this change was correlated with training in the case of Cu, Mn, Se and Zn. All results are expressed in μg/g Hb. Conclusions: We can conclude that physical training produces a decrease in erythrocyte concentrations of Cu, Mn, Se and Zn, which can cause a decrement in athletes' performance given the importance of these elements. For this reason, erythrocyte monitoring during the season would seem to be advisable to avoid negative effects on performance.